2003
DOI: 10.1097/00126334-200311010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal HIV and Malaria Infection on Pregnancy and Perinatal Outcome in Zimbabwe

Abstract: Women with single HIV or malaria infection have a significantly increased risk of adverse outcomes of pregnancy and childbirth. Dual infection has additional detrimental effects on maternal and infant survival in an area where HIV and malaria coexist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 21 publications
4
74
4
1
Order By: Relevance
“…[37][38][39] Paritys specific immunity appears to be reduced in HIVspositive women; women of all parities have a higher relative risk for malaria if they are HIVspositive. 27,37,39,40 This in turn may lead to an even higher rate of adverse pregnancy outcomes, als s though we did not observe this, with the exception of a univariate effect of HIV on stillbirth. Any effect on pregnancy outcome may be partially mediated through the effect of HIV infection on malaria and/or anaemia.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…[37][38][39] Paritys specific immunity appears to be reduced in HIVspositive women; women of all parities have a higher relative risk for malaria if they are HIVspositive. 27,37,39,40 This in turn may lead to an even higher rate of adverse pregnancy outcomes, als s though we did not observe this, with the exception of a univariate effect of HIV on stillbirth. Any effect on pregnancy outcome may be partially mediated through the effect of HIV infection on malaria and/or anaemia.…”
Section: Discussioncontrasting
confidence: 62%
“…7,13,27 However, in many African populations without access to screening, maternal syphilis will remain the most important preventable cause of stillbirth. 7 Efforts to screen and treat for this infection must be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with studies that showed increased susceptibility of HIV positive pregnant women to malaria compared to HIV negative [11,12].…”
Section: Discussionsupporting
confidence: 92%
“…There are many maternal conditions potentially associated with stillbirth. Some, such as hypertension and diabetes, are important in all countries, whereas others are context specifi c; for example, high prevalence of syphilis, malaria, or HIV infection 69,70 or maternal undernutrition in low-income countries and obesity or smoking in middle-income and high-income countries. 14 Other risk factors such as female literacy and socioeconomic status are also important and are discussed in other papers in this Series.…”
Section: The Importance Of Maternal Conditions For Stillbirths and Nementioning
confidence: 99%